Early Weight Bearing pada Pasien Post Operasi Fraktur Ekstremitas Bawah - Enny Selawaty Boangmanalu; Masfuri Masfuri; Liya Arista (Jurnal Keperawatan Silampari, 2023)
This study aims to identify and analyze the effectiveness of weight bearing in postoperative lower extremity fractures. The method used is to review the literature results by analyzing data systematically using a checklist of protocols and rules (PRISMA) and for the feasibility of the study results using the PICO framework. Search for articles using three online databases, namely Science Direct, Google scholar, and PubMed. The results showed that the five pieces discussed the impact of early weight bearing on postoperative lower extremity patients with discussions that had a positive effect—withholding weight / early weight bearing results reducing the incidence of thromboembolic disease. Active movement can reduce joint stiffness, maintain muscle mass, and the ability to return to activities. In conclusion, early weight bearing can be used to increase muscle strength after surgery for lower extremity fracture. Keywords: Orthopedic surgery, Lower extremity fracture